Identifying long non-coding RNAs involved in heat stress response during wheat pollen development - Babaei, Saeid; Bhalla, Prem L.; Singh, Mohan B. (Frontiers in Plant Science, 2024)
Wheat is a staple food crop for over one-third of the global population. However, the stability of wheat productivity is threatened by heat waves associated with climate change. Heat stress at the reproductive stage can result in pollen sterility and failure of grain development. This study used transcriptome data analysis to explore the specific expression of long non-coding RNAs (lncRNAs) in response to heat stress during pollen development in four wheat cultivars. We identified 11,054 lncRNA-producing loci, of which 5,482 lncRNAs showed differential expression in response to heat stress. Heat-responsive lncRNAs could target protein-coding genes in cis and trans and in lncRNA-miRNA-mRNA regulatory networks. Gene ontology analysis predicted that target protein-coding genes of lncRNAs regulate various biological processes such as hormonal responses, protein modification and folding, response to stress, and biosynthetic and metabolic processes. We also noted some paired lncRNA/protein-coding gene modules and some lncRNA-miRNA-mRNA regulatory modules shared in two or more wheat cultivars. These modules were related to regulating plant responses to heat stress, such as heatshock proteins and transcription factors, and protein domains, such as MADS-box, Myc-type, and Alpha crystallin/Hsp20 domain. Our results provide the basic knowledge and molecular resources for future functional studies investigating wheat reproductive development under heat stress.